The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1029/2019jb018688
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Structure of Sri Lanka Derived From Joint Inversion of Surface Wave Dispersion and Receiver Functions Using a Bayesian Approach

Abstract: We study the crustal structure of Sri Lanka by analyzing data from a temporary seismic network deployed in 2016–2017 to shed light on the amalgamation process from a geophysical perspective. Rayleigh wave phase dispersion curves from ambient noise cross correlation and receiver functions were jointly inverted using a transdimensional Bayesian approach. The Moho depths in Sri Lanka range between 30 and 40 km, with the thickest crust (38–40 km) beneath the central Highland Complex (HC). The thinnest crust (30–35… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…In order to provide a model with resolution of Vs and Vp/Vs in the upper few km, we combine the complementary sensitivities of Rayleigh-wave phase velocities (upper crust), ellipticity (upper few km), and the initial pulse of teleseismic receiver functions (shallow Vp/Vs ratio and shallow interfaces) to create a self-consistent model at the regional scale across southern California. The idea to combine receiver functions and surface wave data in a Bayesian joint inversion to determine Vs and Vp/Vs is relatively new (Dreiling et al, 2020;Ojo et al, 2019), and only recently shown to be promising in resolving near-surface Vs and Vp/Vs in sediments (Li et al, 2019). By including Vp/Vs as a parameter we are able to fit receiver functions on a regional scale for the first time across 231 Southern California stations, including in basins where receiver functions have long been discarded as nuisance signals or "corrected" with ad-hoc models, as reverberations overprint Moho and other crustal signatures (e.g., Yeck et al, 2013).…”
mentioning
confidence: 99%
“…In order to provide a model with resolution of Vs and Vp/Vs in the upper few km, we combine the complementary sensitivities of Rayleigh-wave phase velocities (upper crust), ellipticity (upper few km), and the initial pulse of teleseismic receiver functions (shallow Vp/Vs ratio and shallow interfaces) to create a self-consistent model at the regional scale across southern California. The idea to combine receiver functions and surface wave data in a Bayesian joint inversion to determine Vs and Vp/Vs is relatively new (Dreiling et al, 2020;Ojo et al, 2019), and only recently shown to be promising in resolving near-surface Vs and Vp/Vs in sediments (Li et al, 2019). By including Vp/Vs as a parameter we are able to fit receiver functions on a regional scale for the first time across 231 Southern California stations, including in basins where receiver functions have long been discarded as nuisance signals or "corrected" with ad-hoc models, as reverberations overprint Moho and other crustal signatures (e.g., Yeck et al, 2013).…”
mentioning
confidence: 99%
“…Lower values of V p /V s (< 1.65) are found in the Espino Graben and Peninsula of Paria. In both regions mafic rocks have been reported as (a) basaltic layers found inside the Espino Graben (e.g., Feo-Codecido et al, 1984) and (b) the dacitic rocks (porphyritic rhyolite; Alvarado, 2005) found in the Serranía del Interior. Our results appear inconsistent with the lithology of the regions, suggesting the values are most likely related to the high density of faults in both areas.…”
Section: P /V S Mapmentioning
confidence: 99%
“…However, our results for the area with the thickest crust are counter-intuitive with regard to standard foreland basin configurations, where the depocenter of the basin is associated with the deepest flexure and the deepest Moho (e.g., Watts, 2001). In the eastern Venezuela Basin, the deepest sediments (∼ 10 km;Feo-Codecido et al, 1984;Di Croce, 1995;Clark et al, 2008;Bezada et al, 2010) are found in the Espino Graben and Maturín sub-basin, located north and northeast of the region with greatest Moho depths. We find the trend and location of the thickest crust are relatively consistent with the location of the contact between the Precambrian basement (i.e., the Guiana Shield extending beneath the sedimentary layers north of the Orinoco River) and the Cambrian basement found between the Espino Graben and the shield (e.g., Feo-Codecido et al, 1984;Di Croce, 1995).…”
Section: Moho Depth From Receiver Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mannar Basin (west of Sri Lanka, partly onshore, Figure 1) has been formed during Gondwana breakup, which initiated at approximately 165 Ma (Royer & Coffin, 1992). A great amount of rifting between India and Sri Lanka together with strike slip movement and anticlockwise rotation of Sri Lanka was responsible for significant widening and rapid subsidence in the basin (Kularathna et al, 2015) and is associated with strong crustal thinning along the west coast.…”
Section: Introductionmentioning
confidence: 99%